Excessive Postoperative Fluid Administration in Infants with Gastroschisis. Issue 8 (August 2016) - Bonasso, Patrick C.; Lucke-Wold, Brandon; Hobbs, Gerald R.; Vaughan, Richard A.; Shorter, Nicholas A.; Nakayama, Don K.
Careful fluid management is a cornerstone of neonatology because the cardiovascular, respiratory, and gastrointestinal systems in the newborn are sensitive to overhydration. Fluid management in gastroschisis is complicated by insensible fluid loss and postoperative third-space fluid shifts. Study of perioperative fluid management in gastroschisis is limited and has not undergone careful scrutiny. We reviewed perioperative fluid administration and urine output in all infants with gastroschisis over a 5-year period. Data included whether the patient underwent primary closure or staged repair, weight, and events during hospitalization (length of hospitalization and duration of gastric decompression, parenteral nutrition, and ventilator support). Paired t test gave statistical comparisons with significance at P < 0.05. From 2010 to 2014, 24 patients underwent abdominal closure, 17 had primary and 7 had staged closures. Fluid administration exceeded 100 mL/kg/d after primary closure, and was significantly higher (>150 mL/kg/d; P < 0.05) after staged closure on postoperative days 0 to 5. Postoperative urinary output exceeded 75 mL/kg/d for all patients, with higher volumes reaching 100 mL/kg/d after staged closure on postoperative days 4 to 6 ( P < 0.05). Two patients died of sepsis. All survivors were discharged with intestinal continuity and gaining weight on oral feeding. Patients with gastroschisis received large volumes of fluid after operation despite similarly high urine output and positive daily fluid balances. The amounts of fluid administered after both primary and staged closure may be excessive and potentially deleterious.